Assistance of Aisyiyah members in Kucur Village, Dau District, Malang Regency in making simplisia - Nurul Mahmudati; Lud Waluyo; Ririn Harini; Khoirin Maghfiroh (Universitas Muhammadiyah Malang, 2025)
This community service aimed to enhance traditional health literacy and the economic value of family medicinal plants through simplisia production. Using the Society Participatory method, 15 Aisyiyah women in Kucur Village, Malang, were trained in: (1) regulations of empirical traditional health services, (2) appropriate technology for simplisia processing, and (3) hands-on mentoring. Results showed a 59% increase in knowledge and 72% improvement in practical skills. The whole-form simplisia produced met BPOM standards and could be used for self-medication or sold as raw material without distribution permits. Participants were also trained in simple powdering methods (e.g., blending) to enhance product utility. The activity demonstrated the efficacy of community-based participatory approaches in integrating health autonomy and local economic development. Equipment limitations highlighted the need for grinders to optimize production. Future recommendations include establishing micro-enterprise groups, regulatory training for commercial herbal products, and program replication in similar rural settings. This initiative serves as a model for sustainable, locally-driven health and economic empowerment.